Posh Anthroponyms in Northern Bulgaria - Petkova, Gergana (Onomástica desde América Latina, 2024)
This study focuses on the most recent trends in the name-giving process among the Bulgarians, citizens of the Northern part of the country, specifically the major settlements in the area including Pleven, Veliko Tarnovo, Ruse, and Varna, over a ten-year research period (2008 – 2018).